The Effect of Roselle on Anxiety in Menopausal Women - Finta Isti Kundarti; Ferena Purwita Sari; Erna Rahma Yani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
The global population of menopausal women in 2021 is 26% of all women and girls. Anxiety is usually caused by the fear of new problems arising and causing mental emotional disturbances. The rate of anxiety symptoms rises from 3.1% prior to menopause, to 7.0% during the transition to menopause, and further to 7.4% in the post-menopausal phase. Treatment of roselle in rats exposed to stress significantly reduced plasma corticosterene levels and increased brain serotonin levels. Gosypetin contained in roselle is effective as anti-depression and anti-anxiety with a dose of 20 mg/kg. Finding out how roselle affected anxiety in postmenopausal women was the goal of this research. The procedure uses a Quasy Experimental design with a control group that includes a pre- and post-test. Respondents used were 90 divided into 2 groups, namely intervention (45 respondents) and control (45 respondents) in Ngadirejo and Semampir Villages, Kediri City. The sampling technique used simple random sampling. The intervention group was given standard care and roselle extract as much as 1 x 1 500 mg for 5 days, while the control group only received standard care. With a p-value of 0.000, the experimental group's Paired Sample T-Test for anxiety revealed statistically significant findings. In contrast, a p-value of 0.572 was observed for anxiety in the control group. On the difference between posttest anxiety p-value 0.021. Roselle can reduce anxiety in menopausal women. This study is expected to help health workers to provide roselle extract to menopausal women who experience anxiety as an alternative treatment.